2x+6-3=12-4x+3

Simple and best practice solution for 2x+6-3=12-4x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6-3=12-4x+3 equation:


Simplifying
2x + 6 + -3 = 12 + -4x + 3

Reorder the terms:
6 + -3 + 2x = 12 + -4x + 3

Combine like terms: 6 + -3 = 3
3 + 2x = 12 + -4x + 3

Reorder the terms:
3 + 2x = 12 + 3 + -4x

Combine like terms: 12 + 3 = 15
3 + 2x = 15 + -4x

Solving
3 + 2x = 15 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
3 + 2x + 4x = 15 + -4x + 4x

Combine like terms: 2x + 4x = 6x
3 + 6x = 15 + -4x + 4x

Combine like terms: -4x + 4x = 0
3 + 6x = 15 + 0
3 + 6x = 15

Add '-3' to each side of the equation.
3 + -3 + 6x = 15 + -3

Combine like terms: 3 + -3 = 0
0 + 6x = 15 + -3
6x = 15 + -3

Combine like terms: 15 + -3 = 12
6x = 12

Divide each side by '6'.
x = 2

Simplifying
x = 2

See similar equations:

| 6=6x-10 | | 15x+6y=35 | | 16x^2-22x=37 | | 3x^2-8x=24 | | 4x+81=x+81 | | 3x^2-5x-6=a | | =75+6*1000 | | -15+8x-3x=7+4x+55 | | 1000=75+6x | | 15x+6y= | | 3xsquared+5x-6=a | | 90/105 | | -12v+19=0 | | -9(-9-p)=12 | | 3(m-z)+5-(2m-z)= | | 3-4x=11+3x-2 | | Y/13=3/17 | | 900=75+6x | | 100=75+6x | | =75+6*12.5 | | y=-25x^3+75x^2+4x-12 | | =75+6x | | .7+x=.20(7+x) | | 1.2+x=.6(4+x) | | 2x+5-x=x+8 | | x^2+4mx+4=0 | | -3(-7+4v)-6=35-2v | | 18x^4-(8x^2)=2 | | x-4+2x*2=2x+4 | | 7+.30x=.20(7+x) | | 0=x^4-9y^2 | | (18x^4)-(8x^2)=2 |

Equations solver categories